2012
DOI: 10.1371/journal.pone.0050061
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity, Ambivalence, and Apprehensions of Taking HIV-1 Pre-Exposure Prophylaxis among Male Couples in San Francisco: A Mixed Methods Study

Abstract: ObjectiveWe conducted a mixed-methods study to examine serodiscordant and seroconcordant (HIV-positive/HIV-positive) male couples' PrEP awareness, concerns regarding health care providers offering PrEP to the community, and correlates of PrEP uptake by the HIV-negative member of the couple.DesignQualitative sub-study included one-on-one interviews to gain a deeper understanding of participants' awareness of and experiences with PrEP and concerns regarding health care providers offering PrEP to men who have sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 25 publications
10
63
0
Order By: Relevance
“…In contrast, in a study conducted in San Francisco with concordant HIV-positive and HIV-discordant male couples, Saberi and colleagues (2012) found that the majority of partnered men did not endorse PrEP and some were concerned about the possible increases in risk compensation as a result of PrEP use. 53 Although this study did not collect qualitative data to examine the reasons why partnered men might be more or less willing to use PrEP, these findings provide support for partnered men's willingness to use PrEP, particularly among certain subgroups of gay male couples. However, future research studies that collect data from a more representative sample of male couples would provide a greater understanding of men's willingness to use PrEP.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, in a study conducted in San Francisco with concordant HIV-positive and HIV-discordant male couples, Saberi and colleagues (2012) found that the majority of partnered men did not endorse PrEP and some were concerned about the possible increases in risk compensation as a result of PrEP use. 53 Although this study did not collect qualitative data to examine the reasons why partnered men might be more or less willing to use PrEP, these findings provide support for partnered men's willingness to use PrEP, particularly among certain subgroups of gay male couples. However, future research studies that collect data from a more representative sample of male couples would provide a greater understanding of men's willingness to use PrEP.…”
Section: Discussionmentioning
confidence: 80%
“…18,19 In order to increase uptake of PrEP, it is critical that we focus attention on how PrEP is being embraced by populations at-risk for HIV. Our understanding of community perspectives of PrEP suggests that there are multiple limitations to accessing it, 10,11,[20][21][22][23][24] and that populations in need might not be receiving information about PrEP. 25 We must also acknowledge that those who are at greatest risk for HIV may be least likely to be aware of its availability or have the means to access it.…”
mentioning
confidence: 99%
“…However, one that did suggested that behavioral interventions to improve utilization should be targeted to sex-partner type, given that main partners were viewed as a support for taking PrEP but casual partners were associated with barriers to PrEP disclosure. 22 One study of MSM couples found that participants' concerns about risk compensation may decrease their interest in PrEP, 23 and another study found that concerns about intermittent use was considered a barrier to PrEP use. 24 In contrast, higher HIV risk perception, intimacy motivations for condomless sex, recent condomless anal sex with outside partners, education, and age were each independently associated with PrEP adoption intentions.…”
mentioning
confidence: 99%